Design and performance optimisation of the Hexaboards for CMS HGCAL silicon sensor readout electronics. (15th March 2023) - Khan, F.A.; ,
Abstract: A new high-granularity endcap calorimeter, HGCAL, is foreseen to be installed later this decade in the CMS experiment. We present the design and performance of the Hexaboard, a complex hexagonal multi-layer PCB equipped with multiple HGCROC ASICs to read out the signals from silicon pads with low noise and large dynamic range. The Hexaboards are glued to silicon sensors and connect to their pads via wire bonds through holes in the PCBs. The Hexaboard also connects to mezzanine boards for powering, trigger and data concentration and transfer. More than ten variants of the Hexaboard are required to cover the circular fiducial area of the CMS endcaps. Detailed performance measurements, and comparative PCB simulations using Ansys SIwave, are presented.